Design of a piezo-photocatalytic system using both fluid and visible light as driving energy. (5th December 2022) - Liu, Jinrui; Xie, Zhuojiong; Lin, Jingyuan; Liu, Ziming; Su, Qihang; Peng, Fengping
Abstract : The flow-driven piezo-catalysis has been enhanced under visible light due to injection of hot electrons. Abstract : Converting the naturally available mechanical energy and solar energy into chemical energy holds great promise for exploiting renewables. Here, by coupling the piezoelectric effect of ZnO and the plasmon resonance of Ag nanoparticles, we construct a binary catalytic system, which can capture hydromechanical energy from fluids and visible light energy from sun to drive the degradation of tetracycline. Our research demonstrated that the mechanical stirring induced an inner electric field across the piezoelectric ZnO, while the light irradiation triggered plasmonic hot carriers in Ag NPs. These hot carriers injected into ZnO would be utilized to drive piezoelectric catalytic reactions. Our study broadens the horizon of piezo catalysis by utilizing low-density mechanical energy and coupling it with plasmonic photocatalysis.